Identification of β-Caryophyllene (BCP) in Aceh patchouli essential oil (PEO) using gas chromatography-mass pectrophotometry (GC-MS). Issue 1 (February 2021) - Sufriadi, E; Meilina, H; Munawar, A A; Muhammad, S; Idroes, R
Abstract: This study aimed to determine the composition of β-Caryophyllene (BCP) content in patchouli oil from various regions in Aceh. The data from GC-MS analysis can also describe the type of BCP isomer most commonly found in Aceh patchouli. This research used Aceh Pogostemon cablin Benth patchouli oil from 17 different locations. Samples were analyzed using TSQ™ 9000 Triple Quadrupole GC-MS/MS (Thermo Scientific) with TraceGOLD TG-1MS GC Columns. The mean BCP retention time was 14.64 minutes, with a standard deviation (SD) of 0.16. Only one type of BCP compound isomer appeared, namely Bicyclo [7.2.0] undec-4-ene, 4, 11, 11-trimethyl-8-methylene-, [1R- (1R*, 4Z, 9S*)]. The results also showed that the average BCP level was 5.51%. Aceh patchouli contains a much higher BCP level than the minimum commercial target (3.4-3.5%). The MS spectrum data also showed a high similarity between the patchouli oil sample fragmentation and the compound library.